Stability, Thermal Conductivity, Viscosity, and Tribological Characterization of Zirconia Nanofluids as a Function of Nanoparticle Concentration. Issue 1 (2nd January 2020) - Thrush, Steven J.; Comfort, Allen S.; Dusenbury, James S.; Xiong, Yuzan; Qu, Hongwei; Han, Xue; Schall, J. David; Barber, Gary C.; Wang, Xia
Abstract: Commercially prepared spherical zirconia (ZrO2 ) nanoparticles with an average particle diameter of 5 nm and functionalized with a hydrocarbon ligand were dispersed in a polyalphaolefin (PAO) base oil, producing a 10-nm stabilized zirconia nanofluid. The resulting nanofluid's properties were characterized, including thermal conductivity and viscosity. A preliminary study of the nanofluid's ability to generate protective tribofilms was conducted. Long-term stability was verified using dynamic light scattering (DLS) and average particle size was quantified as a function of time. A 10 wt% ZrO2 nanofluid maintained a 10-nm average particle size over 25 months, with no signs of agglomeration or sedimentation, and redispersion was not necessary before analysis. The tribological performance of several concentrations of ZrO2 nanofluids wasdisc characterized with a ball-on-disc tribometer. Tribofilm growth over time was collected via optical interference imaging. Friction data collected over time are also reported. Nanoparticle concentration was varied to understand its effect on tribofilm growth. The ZrO2 tribofilm morphology and chemistry were characterized using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and transmission electron microscopy (TEM).